2006
DOI: 10.1007/s00421-006-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism in elite male rowers: adaptation to volume-extended training

Abstract: We examined the effect of 6-month volume-extended training on bone metabolism in elite male rowers. Twelve elite male rowers (20.8+/-3.0 years; 192.9+/-4.7 cm; 91.9+/-5.3 kg; body fat 10.1+/-2.3%; VO2max 6.2+/-0.5 l min(-1)) participated in this study. Bone biochemical markers, hormones, bone mineral content (BMC), and bone mineral density (BMD) were assessed before and after training. Average weekly training volume was significantly higher (P<0.05) during the 6 months of heavy training compared to relative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
3
22
0
9
Order By: Relevance
“…Short-and long-term training appears to have beneficial effects on markers of bone formation and bone resorption in adolescents and adults (Eliakim et al 1996(Eliakim et al , 1997Erickson and Vukovich 2010;Jurimae et al 2006;Shibata et al 2003;Woitge et al 1998). There is a pattern of increased levels of markers of bone formation and decreased levels or stabilization of markers of bone resorption as a response to exercise training in adults and adolescents, with limited research in children.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Short-and long-term training appears to have beneficial effects on markers of bone formation and bone resorption in adolescents and adults (Eliakim et al 1996(Eliakim et al , 1997Erickson and Vukovich 2010;Jurimae et al 2006;Shibata et al 2003;Woitge et al 1998). There is a pattern of increased levels of markers of bone formation and decreased levels or stabilization of markers of bone resorption as a response to exercise training in adults and adolescents, with limited research in children.…”
Section: Introductionmentioning
confidence: 97%
“…There is a pattern of increased levels of markers of bone formation and decreased levels or stabilization of markers of bone resorption as a response to exercise training in adults and adolescents, with limited research in children. Most studies examine bone turnover markers at 24-48 h following the last exercise session [see for example, (Eliakim et al 1997;Erickson and Vukovich 2010;Jurimae et al 2006;Woitge et al 1998)]. Such a sampling protocol could preclude the detection of an acute exercise effect or the initial phase of the response to a mechanical stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Some reported no relationship (Jürimäe et al 2006;Prouteau et al 2006;Courteix et al 2007, Sööt et al 2007) and others reported a positive relationship at various bones sites (Muñoz et al 2004;Sööt et al 2007). Nevertheless, Muñoz (2004) suggested that leptin might be a good marker of bone mass in these subjects, and probably in other athletes.…”
Section: Introductionmentioning
confidence: 92%
“…Bone mass adaptations may result principally from increased mechanical strain, as demonstrated by the higher BMD observed in athletes practising sports like volleyball, which generate high weight bearing or impact loading, in comparison with athletes practising sports like swimming, with lower mechanical constraints, and sedentary controls (Creighton et al 2001;Morel et al 2001). Nevertheless, endocrine changes related to physical activity and susceptible to modify bone metabolism, including alterations in testosterone (Maïmoun et al 2003) and leptin (Jürimäe et al 2006) secretion, have also been reported.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation